Outside learning: Blending formal, informal, and non-formal higher education during the COVID-19 Pandemic - Cairns, D. (Handbook of children and youth studies, 2024)
Internationalized higher education underwent dramatic changes during the COVID-19 pandemic, with many mobile students confined to the domestic sphere for prolonged periods. While the dissatisfaction of these students at this time was made quite apparent, limited possibilities for social interaction also had pedagogical consequences, especially in relation to the impact on short duration stays abroad hosted by platforms including the European Commission Erasmus programme. These exchanges have typically entailed a blend of formal, informal and non-formal learning, and intense levels of social interactions. This arrangement became unfeasible during the most intensive lockdowns, with the closure of university campuses and restrictions placed on conviviality effectively moving learning outside its traditional spaces. Using findings of research conducted in Portugal during the initial months of the pandemic, the chapter discusses the pedagogical approach to what is referred to as “credit mobility” and some of the transformations that took place during the pandemic that resulted in a devaluation of the internationalized learning experience. Looking towards future developments, although disruption appears to have been largely temporary, there are potential long-term consequences for students and educators, and belated recognition that non-essential mobility is a contributor to the climate emergency.